IMPLEMENTASI KEBIJAKAN ONLINE SINGLE SUBMISSION RISK BASED APPROACH (OSS-RBA) DALAM PERIZINAN BERUSAHA BERBASIS RISIKO DI DINAS PMPTSP KABUPATEN SUMEDANG - Kamal, Deva Ilham Syibul (JRPA - Journal of Regional Public Administration, 2025)
This study aims to examine the implementation of the Online Single Submission Risk Based Approach (OSS-RBA) Policy in Risk-Based Business Licensing at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Sumedang Regency, obstacles to its implementation, and efforts to overcome these obstacles to implementation. The method used in compiling this thesis is a qualitative method with a descriptive type. The sampling technique used was purposive sampling, with research informants: Secretary of the Sumedang Regency DPMPTSP Service, Head of the Sumedang Regency DPMPTSP Licensing Division, Public Complaints Analyst for the Sumedang Regency DPMPTSP Licensing Division, Executive Member of the Sumedang Regency DPMPTSP Licensing Division, Community. Data collection techniques through literature studies and field studies. In analyzing the data used the Miles and Hubernam model with the following steps: data reduction, data presentation, conclusion or verification and triangulation.Based on the results of the study, it was concluded that the Online Single Submission Risk Based Approach (OSS-RBA) Policy in Risk-Based Business Licensing at the Sumedang Regency Investment and One-Stop Integrated Service Agency (DPMPTSP) was implemented quite well. However, in its implementation there are several obstacles experienced, one of which is the minimal participation of the community due to limited access, unwillingness to learn technology and assuming that making permits is complicated, so that the implementation of this policy does not run effectively and optimally in overcoming these obstacles, socialization and education are carried out comprehensively to remote villages to the community. Suggestions related to this study are to increase training programs for the community, especially those who do not understand technology, such as the elderly and business actors in remote areas. To improve understanding of technology, especially for the elderly and business actors in remote areas, it is necessary to hold simple face-to-face or online training with direct assistance from officers.